If p(x) = x + 3, then p(x) + p(-x) is equal to (A) 3 (B) 2x (C) 0 (D) 6

The correct answer is (D) 6

Solution

p(x) = x + 3

p(– x) = – x + 3

Hence

p(x) + p(–x) = (x + 3) + (– x + 3)

= x + 3 – x + 3

= 6

Was this answer helpful?

 
   

0 (0)

(0)
(0)

Choose An Option That Best Describes Your Problem

Thank you. Your Feedback will Help us Serve you better.

Leave a Comment

Your Mobile number and Email id will not be published. Required fields are marked *

*

*

BOOK

Free Class

Ask
Question